Developing evaluation index system for “New Medicine” construction in Chinese medical schools—meta-ethnography and Delphi-AHP approach - Zheng, Dandan; Che Hassan, Norlizah; Ghazali, Norliza; Chai, Yuee; Zhang, Dan; Lyu, Wanru (Frontiers Media SA, 2026)
Objective: This study intends to construct a scientific, comprehensive and operable evaluation index system for the constructing achievements of “New Medicine” in medical schools and contribute to promoting the innovative development of medical education in China. Methods: The study adopted a sequential mixed-methods design. An initial indicator system was first constructed through meta-ethnographic analysis, which was subsequently refined through two rounds of Delphi consultations by 12 experts. In the final stage, the relative weights of the indicators were quantified and validated using the Analytic Hierarchy Process (AHP). Results: The final evaluation index system includes 11 first-level indicators and 37 second-level indicators. Among them, the top three first-level indicators with the highest weight coefficients are the reform of the curriculum system (0.1790), the education and training of medical students (0.1550), and the optimization and adjustment of the structure of disciplines and majors (0.1530), emphasizing the fundamental role of these three in school’s medical education, while the stakeholder feedback mechanism (0.0190) is used as a supplementary element. Conclusion: This study constructs an scientifically grounded evaluation index system for the development of “New Medicine” in medical schools, addressing the current lack in existing research of quantifiable measures for assessing medical innovation education in the new era. Meanwhile, it can serve as a reference for relevant researches on medical education reform, and provide evaluation benchmark for education regulatory departments, policy makers, as well as medical school administrators.